Synthesis and optical characterization of chitosan capped gold nanoparticles via chemical reduction technique / Norfazila Mohd Sultan - Norfazila, Mohd Sultan (2013)
The simple route of synthesizing gold nanoparticles via chemical reduction technique was implemented. The main focus of this study is to achieve enhanced properties of gold nanoparticles by regulating the process parameters of the synthesis. The correlation of the process parameters and resultant size of gold nanoparticles has been deliberated. The gold nanoparticles were reduced with monosodium glutamate (MSG) and further capped with chitosan to prevent agglomeration between particles. The samples were characterized with several characterization techniques. The TEM micrograph showed dispersed particles with narrow size distribution of capped gold nanoparticles with the most probable particles size distributed in the range of 16 to 18 nm. The most stable gold nanoparticles occurred after reduced with 100 mM of MSG and capped with 1g of chitosan where the SPR peaks were blue shifted as the concentration of reducing agent increases and decreasing pattern of FWHM was recorded. Gold nanoparticles capped with chitosan remain small in size after aged for 1 month compared to uncapped gold nanoparticles. Gold nanoparticles exhibit sharper absorbance peak at longer relaxation time. The Gibbs free energy (GFE) of chitosan-capped gold nanoparticles reduced with 50 mM of MSG calculated as 12.22 KJ/mol and the equilibrium constant, Keq was computed to be 0.0219 mol L-1. The ability of chitosan capped gold nanoparticles to uptake analytes was studied by employing amorphous carbon nanotubes (α- CNT), copper oxide (Cu2O) and zinc sulphate (Zn SO4) as the target materials. The absorption spectra showed dramatic peak intensity increased and red shifted SPR peak once the analytes were added to the chitosan capped gold nanoparticles.